KUALITAS PELAYANAN PERPUSTAKAAN KELILING DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Fepi Febianti; Kuswara (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
Mobile libraries are one of the programs of public libraries to serve people who are not reached or difficult to reach by public library services, considering the limitations and weaknesses of public libraries. One of the purposes of mobile library services is to provide information and science services more closely. The Regional Public Library and Archives Office of Sumedang Regency is a government facility as a service to the community, which aims to provide sources of information materials in the form of reading books and other archives. The methods used in this study are descriptive survey methods and literature studies. The descriptive method is a method that seeks to solve or answer the problems faced in the current situation. Based on the analysis and discussion, it was concluded that the quality of mobile library services at the Archives and Library Office has not been effective and efficient in meeting the needs of the community. The quality of service from the tangible aspect is the condition of the vehicle that only has 1 functioning so it is difficult to reach many areas. The quality of service from the aspect of reliability, namely scheduling in mobile library services, has not been well scheduled. Even for routine schedules have not been implemented. The quality of service from the aspect of responsiveness is that the service of librarians is not good because it does not quickly respond to the needs of visitors and cannot help visitors who have difficulty finding books optimally. The quality of service from the assurance aspect, namely the officers have not been friendly and polite, the officers have not been able to answer questions asked by visitors, and there has been no rearrangement of what book collections need to be fulfilled if making a tour visit with the aim of meeting the information needs of the people of Sumedang. The quality of service from the emphaty aspect is that officers have not been able to manage tools in the library. Officers have not been able to help visitors if they have difficulty in finding the information needed.